A combination of ellagic acid and tetracycline inhibits biofilm formation and the associated virulence of Propionibacterium acnes in vitro and in vivo. Issue 4 (20th April 2016) - Sivasankar, Chandran; Maruthupandiyan, Shanmugam; Balamurugan, Krishnaswamy; James, Prabhanand Bhaskar; Krishnan, Venkat; Pandian, Shunmugiah Karutha
Abstract: Propionibacterium acnes is an opportunistic pathogen which has become notorious owing to its ability to form a recalcitrant biofilm and to develop drug resistance. The current study aimed to develop anti-biofilm treatments against clinical isolates of P. acnes under in vitro and in vivo conditions. A combination of ellagic acid and tetracycline (ETC; 250 μg ml −1 + 0.312 μg ml −1 ) was determined to effectively inhibit biofilm formation by P. acnes (80–91%) without affecting its growth, therefore potentially limiting the possibility of the bacterium attaining resistance. In addition, ETC reduced the production of extracellular polymeric substances (EPS) (20–26%), thereby making P. acnes more susceptible to the human immune system and antibiotics. The anti-biofilm potential of ETC was further substantiated under in vivo conditions using Caenorhabditis elegans . This study reports a novel anti-biofilm combination that could be developed as an ideal therapeutic agent with broad cosmeceutical and pharmaceutical applicability in the era of antibiotic resistance.